The Community Youth Outreach Programme in Delta, British Columbia, Canada:"The Personal Touch That Works" - Chan, Sherman; Thind, Hardeep; Lim, Lesley (Refuge: Canada's Journal on Refugees, 2000)
With Canada's strong multicultural policy, immigrants are encouraged to maintain their cultural values and expectations while adjusting to a new country. This in mind, the Surrey Delta Immigrant Services Society partnered with the British Columbia Ministry Responsible for Multiculturalism and Immigration, British Columbia Ministry for Children and Families, and the Delta School District to develop a programme which assists new immigrant youth, their families and their community. It provides an innovative approach to assist with language and cultural interpretation as well as school-based initiatives for all parties involved. Thus, this paper is a description of the Community Youth Outreach Programme in Delta, British Columbia and a discussion of the key features that address the needs of immigrant and refugee students and their families while affirming their culture and linguistic background in a demographically dynamic area.